OBSERVASI HILĀL DI INDONESIA DAN SIGNIFIKANSINYA DALAM PEMBENTUKAN KRITERIA VISIBILITAS HILĀL - Muh. Ma'rufin Sudibyo (Al-Ahkam, 2014)
This research aim to analyze of the data generating a modern empirical visibility criterion called Indonesia visibility criteria (RHI criteria) in the form aD ³ 0,099 DAz2-1,490 DAz + 10,382. Although based on a local database, but these criterion are consistent with the international visibility databases such as Yallop and ICOP, along selected only for data sourced from the tropical region. These criterion also were consistent when compared to the tropical visibility database not from Indonesia. So this criteria is the national visibility criterion (for Indonesia) and also regional visibility criterion (tropical region). Comparative analysis showed that although different in form than modern visibility criterion that have similar variables as Fotheringham-Maunder and Bruin criterion, but the form of the Indonesia visibility criterion (RHI criterion) may still be accepted because it is supported by the recent observation data. The difference in shape is due to the Indonesia visibility criterion (RHI criterion) does not distinguish between optical aid-based observations with naked-eye observations.